2006
DOI: 10.1007/s10875-006-8144-1
|View full text |Cite
|
Sign up to set email alerts
|

Infants Presenting with Recurrent Infections and Low Immunoglobulins: Characteristics and Analysis of Normalization

Abstract: To better characterize infants presenting with diminished immunoglobulin levels and intact antibody formation, we present 49 such infants, correlating presenting characteristics with history and time to immunoglobulin normalization. Term infants with the following characteristics were included: 1) one or more immunoglobulin classes > 2SD below mean, 2) protective antibody titer to tetanus and diphtheria, 3) intact cellular immunity, 4) no features of other syndromes. The children were 69.4% male and had recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 12 publications
5
33
0
4
Order By: Relevance
“…In agreement with previously reported findings, [8] male infants resolved more quickly than females (p=0.001). The median time to resolution in males was 13 months with 73% resolving in 3 years.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previously reported findings, [8] male infants resolved more quickly than females (p=0.001). The median time to resolution in males was 13 months with 73% resolving in 3 years.…”
Section: Resultssupporting
confidence: 93%
“…[7] At the time of initial recognition of hypogammaglobulinemia in an infant, since this may be physiologic, immunologists are often finding with clinically relevant questions regarding the likely duration of hypogammaglobulinemia. Previous studies have shown that males are more likely than females to have resolution of hypogammaglobulinemia during infancy, [8] however, other than this observation, there has been little information that would allow an informed prediction about the probable time to resolution to hypogammaglobulinemia. The goal of this study was to define parameters, present at the time of diagnosis that might predict time to resolution of hypogammaglobulinemia.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Whealan ve ark. (21) hipogamaglobülinemi tanısı ile izlenen 49 olgunun tamamı-nın difteri ve tetanos aşı yanıtlarının olduğu bildirmiş-tir. Mammedova ve ark.…”
Section: İstatistiksel Analizunclassified
“…Recurrent wheezing resistant to β2 adrenergic-agonist and anti-cholinergic therapies are usually investigated for hypogammaglobulinemia. In fact, recurrent viral infections including lower respiratory tract infections have been reported as associated to transient hypogammaglobulinemia of infancy (THI) [1][2][3][4][5]. Yet, the main clinical feature in patients affected by infantile hypogammaglobulinemia remains recurrent infections.…”
Section: Introductionmentioning
confidence: 99%